2020
DOI: 10.1101/2020.03.03.973131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neural code for egocentric spatial maps in the human medial temporal lobe

Abstract: Spatial navigation relies on neural systems that encode spatial information relative to the external world or in relation to the navigating organism. Ever since the proposal of cognitive maps, the neuroscience of spatial navigation has focused on allocentric (world-referenced) neural representations such as place cells. Here, using single-neuron recordings during virtual 30 navigation, we reveal a neural code of egocentric (self-centered) spatial information in the human brain: We describe "anchor cells", whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 81 publications
(59 reference statements)
5
29
0
Order By: Relevance
“…Subsequent fMRI-experiments in humans with a highly similar task showed that sequence-based navigation activates the left and landmark-based navigation activates the right hippocampus (Iglói et al, 2010). The impairments observed here fit these observations and further suggest that hippocampus-dependent networks provide computations relevant to early consolidation of allocentric as well as egocentric memory representations (Kunz et al, 2020;Johnsen and Rytter, 2021;Samanta et al, 2021). Alternatively, at least in our task, administration of propofol may have affected a central spatio-temporal binding process that yields seemingly distinct behavioral manifestations -depending on the particular navigational context imposed by the experimenter.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Subsequent fMRI-experiments in humans with a highly similar task showed that sequence-based navigation activates the left and landmark-based navigation activates the right hippocampus (Iglói et al, 2010). The impairments observed here fit these observations and further suggest that hippocampus-dependent networks provide computations relevant to early consolidation of allocentric as well as egocentric memory representations (Kunz et al, 2020;Johnsen and Rytter, 2021;Samanta et al, 2021). Alternatively, at least in our task, administration of propofol may have affected a central spatio-temporal binding process that yields seemingly distinct behavioral manifestations -depending on the particular navigational context imposed by the experimenter.…”
Section: Discussionsupporting
confidence: 77%
“…It is however unclear whether these representational modes can be clearly dissociated at the neural level (Ekstrom et al, 2014(Ekstrom et al, , 2017Alexander et al, 2020;Ladyka-Wojcik and Barense, 2021). While hippocampus and adjacent regions of the medial temporal lobe have traditionally been associated with allocentric spatial representations, recent research in animals and humans suggests an important role for egocentric memory as well (Kunz et al, 2020;Johnsen and Rytter, 2021;Samanta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Honeycomb maze reveals the 2D nature of the pre-choice 'subjunctive' representation. 8 and in humans performing a multiple object-in-location VR test 11 . In the present experiment, these occurred in only 14% of the cells during a foraging task, fewer than half of the percentage seen during the navigation task, and further, were not clustered around the concurrent navigation goal.…”
Section: Discussionmentioning
confidence: 99%
“…When a goal is introduced, place cells become directional 8 and their fields move in the direction of the goal when it is moved 9 . Recent work has shown that cells in the dorsal hippocampus encode heading towards a goal and other locations in the bat 10 , mouse7 and human 11 .…”
mentioning
confidence: 99%
“…Vector coding (such as distance and direction) in spatial cognition is common for neurons within and around the hippocampal formation, far from the sensory periphery (Bicanski and Burgess, 2020). The spatial receptive fields (“vector codes”) of these neurons, are often expressed in the allocentric coordinates, such as in the cases of boundary vector cells (Lever et al, 2009), border cells (Solstad et al, 2008), landmark vector cells (Deshmukh and Knierim, 2013), object vector cells (Hoydal et al, 2019), visual cue cells (Kinkhabwala et al, 2020), human anchor cells (Kunz et al, 2021), border-elicited theta oscillation (Stangl et al, 2021), primate border cells (Killian et al, 2012) and vector trace cells (Poulter et al, 2021). Recently, egocentric representations of space have been reported in the PPC, RSC, lateral EC (LEC), postrhincal cortex, postsubiculum and dorsomedial striatum (Gofman et al, 2019; LaChance et al, 2019; Peyrache et al, 2017; Wang et al, 2018).…”
Section: Disucssionmentioning
confidence: 99%